Assessment of mariculture-derived microplastic pollution in Dapeng Cove, China - Xu, Yong; Li, Shilin; Chen, Jianlei; Cui, Zhengguo (Frontiers in Marine Science, 2024)
Marine microplastic pollution just as ocean acidification and greenhouse effect has attracted much environmental concern and become a hot research subject for marine researchers globally. The abundances, distribution, and characteristics of microplastics in surface seawater and sediments from Dapeng Cove were investigated in this study. The results indicated that the abundance of microplastics was 1333 ± 773 items/m3 in surface seawater and 1381 ± 1021 items/kg in sediments, showing a medium microplastic pollution level compared with other sea areas. Fibers were the prevailing shapes of microplastics in both surface seawater and sediments, representing 65.4% and 52.1% of the total microplastic numbers, respectively. Moreover, small microplastics (<1mm) in surface seawater and sediments accounted for 69.6% and 62.2%, respectively. According to the identification by Fourier Transform Infrared microscope (micro-FTIR), the main composition of microplastics in surface seawater and sediments was polyethylene (PE) or polypropylene (PP). It is necessary to enhance the regulation of current plastic products used in aquaculture, reduce the production and release of microplastics during the mariculture process, and develop alternatives to plastic fishing gear. The results of this study suggested that long-term mariculture development had caused the accumulation of a large amount of microplastics in water and sediments in Dapeng Cove. We constructed the first basic data of microplastics pollution about Dapeng Cove. This study will serve as a reference for further studies of the distribution and migration of microplastics in mariculture zones.